2021
DOI: 10.1021/acs.inorgchem.1c03498
|View full text |Cite
|
Sign up to set email alerts
|

MOF-on-MOF Strategy to Construct a Nitrogen-Doped Carbon-Incorporated CoP@Fe–CoP Core-Shelled Heterostructure for High-Performance Overall Water Splitting

Abstract: The design and preparation of efficient and low-cost catalysts for water electrolysis are crucial and highly desirable to produce eco-friendly and sustainable hydrogen fuel. Herein, we prepared nitrogen-doped carbon-incorporated CoP@Fe–CoP core-shelled nanorod arrays grown on Ni foam (CoP@Fe–CoP/NC/NF) through phosphorization of ZIF-67@Co–Fe Prussian blue analogue (ZIF-67@CoFe–PBA). The hierarchical nanorod arrays combined with the core-shelled structure offer favorable mass/electron transport capacity and max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…5b shows the CV curves at a fixed scan rate of 50 mV s −1 , in which the anode peak currents increase significantly after continuously adding the glucose concentration in the range of 0 to 4 mM on account of the excellent electrocatalytic oxidation activity. 30,31 Through electrochemical impedance spectroscopy (EIS), it is not difficult to find that the impedance for the phosphatized sample of Cu-BTC-CP is lower than the carbonized Cu-BTC-C with a larger slope value within the low-frequency region (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
“…5b shows the CV curves at a fixed scan rate of 50 mV s −1 , in which the anode peak currents increase significantly after continuously adding the glucose concentration in the range of 0 to 4 mM on account of the excellent electrocatalytic oxidation activity. 30,31 Through electrochemical impedance spectroscopy (EIS), it is not difficult to find that the impedance for the phosphatized sample of Cu-BTC-CP is lower than the carbonized Cu-BTC-C with a larger slope value within the low-frequency region (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 778.36 and 793.26 eV are assigned to the Co 2+ 2p 3/2 and 2p 1/2 of Co−P bonds, and the peaks with binding energies of 781.57 and 797.57 eV are attributed to the oxidized Co 3+ species owing to the surface oxidation. 39,40 Notably, compared with the FeP-CoP, both the doublets belonging to Fe−P and Co−P of the FeP-CoP/Ti 3 C 2 T x -5 shift negatively, suggesting the strong coupling interaction between FeP-CoP and Ti 3 C 2 T x MXene. 41,42 Meanwhile, the peaks indexed to oxide species of Fe and Co become more obvious for FeP-CoP/Ti 3 C 2 T x -5, owing to the surface oxidation of phosphides with a smaller size.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In order to overcome the above intrinsic defects of Co-based phosphides, it has been a common strategy to introduce second or third phase metal elements to construct bimetallic or trimetallic phosphides. It is reported that the introduction of second or third phase metal elements (such as Fe, Ni, Mo, Cu, Mn, and so on) can effectively optimize surface electronic structure of Co-based phosphides and expose them to more active centers, which will improve their inherent electrocatalytic activity. For example, it was shown that an Fe-doped CoP nanoarray exhibited outstanding HER and OER performance, which further facilitated showing that it exhibited a low cell voltage of 1.60 V to drive an overall water-splitting current of 10 mA/cm 2 in a symmetrical two electrode system . Among various metal elements for the doping of Co-based phosphides, manganese (Mn) is particularly promising because of its extremely higher electronegativity compared with most of the common metal elements, which can greatly promote electronic transmission and tailor the electronic structure. However, due to the limitation of active site exposure and charge transfer capacity, their electrocatalytic performances are still not ideal, especially in overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the doping of metal elements, constructing a heterogeneous interface by integration of different catalysts into a multiphase core–shell structure is another effective means to improve the electrocatalytic performance of Co-based phosphide catalysts. , It was shown that abundant heterogeneous interfaces not only can expose more reactive sites and accelerate the electron transport rate but also can realize synchronous adsorption of reaction intermediates. For instance, it was shown that CoP/NiCoP hybrid nanosheet networks exhibited outstanding HER activity with an ultralow overpotential of 75 mV to deliver a current density of 10 mA/cm 2 .…”
Section: Introductionmentioning
confidence: 99%